PROMISE of Coronary CT Angiography: Precise and Accurate Diagnosis and Prognosis in Coronary Artery Disease. Issue 4 (April 2016) - Thomas, Dustin M.; Branch, Kelley R.; Cury, Ricardo C.
Abstract : Abstract: Coronary computed tomography angiography (CCTA) is a rapidly growing and powerful diagnostic test that offers a great deal of precision with respect to diagnosing coronary artery disease (CAD). Guideline statements for patients with stable ischemic heart disease have recommended CCTA for only a limited portion of intermediate-risk patients who have relative or absolute contraindications for exercise or vasodilator stress testing. The publication of two large, prospective randomized clinical trials, the Prospective Multicenter Imaging Study for Evaluation of Chest Pain and the Scottish Computed Tomography of the Heart Trial are likely to expand these indications. These new data from large trials, in addition to other studies, show that CCTA is highly sensitive for the detection of CAD, identifies high-risk patients for cardiac events based on extent or plaque morphology of CAD that would not be identified by other noninvasive means, and provides significantly greater diagnostic certainty for proper treatment, including referral for invasive coronary angiography with revascularization more appropriately. Superior diagnostic accuracy and prognostic data with CCTA, when compared with other functional stress tests, may result in a reduction in unnecessary downstream testing and cost savings. In addition, newer CCTA applications hold the promise of providing a complete evaluation of a patient's coronary anatomy as well as a per-vessel ischemic evaluation. This review focuses on the interval knowledge obtained from newer data on CCTA in patients with stable ischemic heart disease, primarily focusing on the contributions of the Prospective Multicenter Imaging Study for Evaluation of Chest Pain and the Scottish Computed Tomography of the Heart Trial. Abstract : Coronary CT angiography (CCTA) is a powerful diagnostic test that offers a great deal of precision and accuracy with respect to diagnosing coronary artery disease (CAD). The publications of the Prospective Multicenter Imaging Study for Evaluation of Chest Pain trial and the Scottish Computed Tomography of the Heart Trial provide important additional knowledge with respect to the prognosis and diagnosis of CAD in patients with stable ischemic heart disease. CCTA improves diagnostic certainty and identifies nests of high-risk patients with obstructive as well as nonobstructive CAD, resulting in appropriate changes in medical therapy and potential improvement in patient outcomes while reducing unnecessary downstream testing. These data lend further credibility to the use of CCTA as a first-line therapy in patients with suspected CAD.